Implementasi Perkawinan Beda Agama Terhadap Suami Isteri yang Berbeda Keyakinan - Sarah, Putri; Sulastri, Sulastri (Nagari Law Review, 2024)
Interfaith marriage is a complex issue in Indonesia, considering the conflict between religious norms and state law. Based on Law Number 1 of 1974 concerning Marriage, the validity of a marriage is determined by the laws of each religion, which often becomes an obstacle for interfaith couples, especially in registering their marriage. This study examines the legality of interfaith marriages in Indonesia through the Yogyakarta District Court Determination Number 141/Pdt.P/2023/PN Yyk and its implications for the rights and obligations of husbands and wives with different beliefs in Indonesian family law. This research uses a normative juridical approach with analysis of court decisions and review of statutory regulations. The research results show that although Indonesian law does not explicitly regulate interfaith marriages, the court decision route can provide a legal solution for registering these marriages. However, the legal implications remain significant, especially in terms of maintenance rights, inheritance rights and child status, which often face administrative obstacles. Therefore, more inclusive regulations and clearer registration procedures are needed to provide legal certainty and protect the rights of families from interfaith marriages. The aim of this research is to provide answers to various problems related to interfaith marriages.